Design a Retaining Wall Using Geopolymer - Chong, En Yong (2015)
Main purpose of this project is to replace standard Concrete with geopolymer concrete. Geopolymer concrete is a “go green” concept where ¡t doesn’t use any cement but only replace with fly-ash and also some alkaline activators. This geopolymer concrete is very suitable to build a retaining wall of a port or harbor and also sewage system due to the high early strength of it and also it is high resistance to corrosion attack. This project will compare the compressive strength of a standard concrete and also the geopolynier concrete by using the same mix proportion to achieve a fair result. Geopolymer concrete will not achieve a high early strength if the procedure and mix proportion are not in order but it still will achieve a strength of a normal concrete. Conclusion that I made is geopolymer can replace standard concrete but high early strength of it it’s not guarantee.